(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the present scenario, the global concentration is on environment sustainability. Everyone wants to become green and eco-friendly and reduce their affect on the environment and reconstruct the environment with clean and healthy practices. Everyone in the supply chain (manufacturer to a customer) is ready to apply green practices in their activities. If the industries produce the products in an environmentally sustainable manner thereby reduce environment impact level. This brings the demand for green production and green products. So the author attempted to assess the product environmental profile through life cycle assessment tool and distinguishes the green product over conventional product. This paper is based on secondary data collected from different sources which include journals, internet and different company websites. The paper primarily focuses on life cycle assessment of product and secondly discusses the comparison of green product over conventional product. The paper assists in a better understanding of the green product and discusses the influencing factors on stakeholders in the conversion process of conventional to green practices.